BERPIKIR KRITIS DAN KREATIF DALAM PENDIDIKAN KRISTEN - Parlindungan Pardede (Program Studi Pendidikan Agama Kristen, 2016)
The challenges of the 21st century caused by the explosion of information and the accelerative increasing changes have been arousing researchers and educators’ awareness of the high importance of developing critical and creative thinking skills among learners. Critical thinking,which is rational, reflective and evaluative,is highly necessary for every individual, especially in such an era marked by a surge of current information. It is of high necessity in any activity of sorting and analyzing information and in solving problem. Creative thinking is a process or an attempt toproduce a new, effective and ethical idea, thought or object. Although they are different, the two modes of thought are closely connected, even complementary. Every person essentially has the potential for critical and creative thinking. However, to be able to use them effectively, they need to be studied and developed. Current research results and experiencesrevealed that critical and creative thinking skills could be developed in the classroom, either integrated with subjects, or through explicit learning. Abstrak: Tantangan abad ke-21yang diakibatkan oleh ledakan informasi dan perubahan-perubahan yang semakin akseleratif telah memicu para peneliti dan pendidik untuk mengembangkan kemampuan berpikir kritis dan kreatif di kalangan peserta didik. Berpikir kritis yang bersifat rasional, reflektif dan evaluatif sangat dibutuhkan setiap individu untuk memilah dan menganalisis informasi dan untuk memecahkan masalah, khususnya di era yang ditandai dengan luapan informasi saat ini. Berpikir kreatif merupakan proses atau upaya untuk menghasilkan ide, pemikiran atau objek orisinal atau baru yang efektif dan etis. Meski berbeda, kedua mode berpikir ini berhubungan erat, bahkan saling melengkapi. Setiap orang pada hakikatnya memiliki potensi pemikiran kritis dan kreatif. Namun, agar dapat digunakan secara efektif, keduanya perlu dipelajari dan dikembangkan, dan hal ini sangat sesuai dilakukan di kelas, baik secara terintegrasi dengan mata pelajaran, maupun melalui pembelajaran eksplisit.